The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1530/eje-13-0231
|View full text |Cite
|
Sign up to set email alerts
|

Safety of long-term treatment with cabergoline on cardiac valve disease in patients with prolactinomas

Abstract: Objective: Cabergoline (CAB) has been found to be associated with increased risk of cardiac valve regurgitation in Parkinson's disease, whereas several retrospective analyses failed to detect a similar relation in hyperprolactinemic patients. The current study aimed at investigating cardiac valve disease before and after 24 and 60 months of continuous treatment with CAB only in patients with hyperprolactinemia. Subjects and methods: Forty patients (11 men and 29 women, aged 38.7G12.5 years) newly diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 46 publications
1
39
0
Order By: Relevance
“…Follow-up was at least one year, but the median follow-up was much longer, at nearly 10 years and the cumulative median dose of cabergoline was >277 mg. None of the handful of moderate mitral or tricuspid regurgitation cases noted at baseline worsened significantly during follow-up. These results are in keeping with other data from prospective analyses [33][34][35]; however, in contrast to Delgado et al, we did not identify any cases of significant calcification despite similar mean ages at diagnosis in the two studies. Many factors can influence valvular calcifications (dyslipidemia, age, hypertension, renal failure, hyperphosphatemia) and discrepancies between studies might be explained by differences in the populations studied.…”
Section: Discussionsupporting
confidence: 90%
“…Follow-up was at least one year, but the median follow-up was much longer, at nearly 10 years and the cumulative median dose of cabergoline was >277 mg. None of the handful of moderate mitral or tricuspid regurgitation cases noted at baseline worsened significantly during follow-up. These results are in keeping with other data from prospective analyses [33][34][35]; however, in contrast to Delgado et al, we did not identify any cases of significant calcification despite similar mean ages at diagnosis in the two studies. Many factors can influence valvular calcifications (dyslipidemia, age, hypertension, renal failure, hyperphosphatemia) and discrepancies between studies might be explained by differences in the populations studied.…”
Section: Discussionsupporting
confidence: 90%
“…This medication was discontinued for the treatment of Parkinson's disease; however, because the dose used in the treatment of pituitary adenomas is much lower, the drug continued to be used in this setting. Subsequently, there were several studies addressing the risk of valvar damage in prolactinoma and acromegaly patients, without clear evidence of clinically significant valvar disease [12,[40][41][42]. The majority of the studies evaluated patients treated for hyperprolactinemia, and the follow-up times were short to assure that CAB was not associated with a risk for valvar disease in the doses used in acromegaly treatment [40,41,43,44].…”
Section: Side Effectsmentioning
confidence: 99%
“…However, a large register study of Parkinson's disease carried out in 2007 has documented an increased risk of valvulopathy in patients treated with a cabergoline dose higher than 3 mg/day (93), and Zanettini et al (94) reported an association between cumulated doses of cabergoline and valvulopathy. From 2008 to the present, 16 clinical studies have been published on dopamine agonists -primarily cabergoline -and valvulopathy in patients with hyperprolactinaemia (95). The conclusions from these clinical studies were reassuring, and a register study found no association between clinically significant cardiac valve disease and cabergoline therapy in patients with hyperprolactinaemia (96).…”
Section: Medical Therapy For Acromegalymentioning
confidence: 99%